Caracterización de la diversidad morfológica y molecular (adn) de cucurbita maxima duch. c. moschata duch. y c. pepo l. de la Región Lambayeque - Estela Campos, César (2009)
The characterization of morphological diversity and molecular (DNA) of two cultivars of Cucurbita maxima Duch., C. moschata Duch. and C. pepo L. of the Lambayeque region, was performed using morphological traits and four microsatellites molecular markers of Cucurbitaceae. We used the IPGRI descriptor for cucurbits. The design of randomized complete block (BCA) was used for morphological and performance evaluations of the cultivars. In the analysis of the molecular characterization was determined coefiiente Jaccard similarity, genetic diversity index of Nei. Morphological analysis of cultivars of the species studied showed great variability of shape, color, fruit weight, petiole length, internode, etc. The total number of alleles found was 34. The similarity coefficients ranged from 0.603-0.728. The rate of heterozygosity (He) was 0.495, 0.463 and 0.476 for C. pepo L., C. maxima Duch. and C. moschata Duch. respectively. The microsatellite CMTP 21 presented the highest rate of polymorphism information.